Called to Collaboration: The University Consortium for Catholic Education - Davies, Molly; Kennedy, Karen (Catholic Education: A Journal of Inquiry and Practice, 2009)
This article describes the University Consortium for Catholic Education (UCCE) as an example of collaboration between Catholic colleges, universities, schools, and other stakeholders. The UCCE supports a collaborative cadre of primarily Catholic colleges and universities as they design and implement graduate level teaching service programs for the purpose of supporting K-12 Catholic education in the United States. The article provides a brief introduction to the work of the consortium and analyzes its impact through the lens of Archbishop Michael Miller’s (2006) five benchmarks of truly Catholic schools. The authors collected data and testimony from UCCE program directors, current participants, and alumni to describe the consortium’s model for Catholic teacher preparation, to demonstrate the centrality of collaboration for the success of a program, and to testify to the impact of programs on participants and Catholic colleges and schools.